Recent advances in porous nanomaterials-based drug delivery systems for cancer immunotherapy - Su-Ran Li; Fang-Yi Huo; Han-Qi Wang; Jing Wang; Chun Xu; Bing Liu; Lin-Lin Bu (Journal of Nanobiotechnology, 2022)
Abstract Cancer immunotherapy is a novel therapeutic regimen because of the specificity and durability of immune modulations to treat cancers. Current cancer immunotherapy is limited by some barriers such as poor response rate, low tumor specificity and systemic toxicities. Porous nanomaterials (PNMs) possess high loading capacity and tunable porosity, receiving intense attention in cancer immunotherapy. Recently, novel PNMs based drug delivery systems have been employed in antitumor immunotherapy to enhance tissue or organ targeting and reduce immune-related adverse events. Herein, we summarize the recent progress of PNMs including inorganic, organic, and organic–inorganic hybrid ones for cancer immunotherapy. The design of PNMs and their performance in cancer immunotherapy are discussed in detail, with a focus on how those designs can address the challenges in current conventional immunotherapy. Lastly, we present future directions of PNMs for cancer immunotherapy including the challenges and research gaps, providing new insights about the design of PNMs for efficient cancer immunotherapy with better performance as powerful weapons against tumors. Finally, we discussed the relevant challenges that urgently need to be addressed in clinical practice, coupled with corresponding solutions to these problems.